2022
DOI: 10.4149/neo_2021_211025n1521
|View full text |Cite
|
Sign up to set email alerts
|

Periostin: a predictable molecule to prognosis and chemotherapy responses of gastrointestinal and hepato-biliary-pancreatic malignant tumors?

Abstract: understanding of the disease is constantly updated, just as strategies for treating malignant tumors are constantly updated. New diagnoses, follow-up indicators, and treatment plan formulations need more evidence to be supported. To date, radical surgical resection is still the preferred treatment for advanced digestive system malignancies, and combination therapy including chemotherapy and targeted therapy before or after surgery is aimed at improving the prognosis and quality of life of patients. However, if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…It has been well demonstrated that POSTN expression is deregulated in malignant transformation. High POSTN expression levels are usually associated with aggressive tumor behavior and poor prognosis in cancer ( 41 44 ). For example, using immunohistochemical analyses, Hu et al.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well demonstrated that POSTN expression is deregulated in malignant transformation. High POSTN expression levels are usually associated with aggressive tumor behavior and poor prognosis in cancer ( 41 44 ). For example, using immunohistochemical analyses, Hu et al.…”
Section: Discussionmentioning
confidence: 99%